Time trap - Farshtey, Greg. (2005)
When Toa Vakama recovers the Mask of Time, there is so much turmoil that he wonders if the fabric of time itself has been torn.
Keywords: LEGO toys -- Juvenile fiction; Heroes -- Juvenile fiction; Space and time -- Juvenile fiction